A Policy for Addressing Menstrual Equity in Schools: A Case Study From New York City, U.S.A. - Schmitt, Margaret L.; Booth, Kathleen; Sommer, Marni (Frontiers in Reproductive Health, 2022)
There has been a growth in menstrual equity policy advancements in the U.S.A. in recent years; with much of the new legislation prioritizing the needs of adolescent girls in schools. New York City, a predecessor of this movement, was the first U.S.A. locality to pass such legislation in 2016. The aim of this case study was to better understand the various factors which led to the development, passage and initial implementation of New York City’s Menstrual Equity in Schools Policy. Data collection methods included a desk review and qualitative assessment with several actors involved across the policy and introduction phases. Key findings included 1) the utility of community narratives and a pilot project as a means for overcoming initial skepticisms, proving feasibility and generating support; 2) the importance of policy champions for overcoming fiscal objections and navigating political discourse; and 3) lessons learned from early implementation efforts, including variance in awareness and distribution models. This case study yields valuable insights into the practical considerations when designing or implementing policies aimed at tackling issues of menstrual equity within school settings.